Impact of pre-existing comorbidities and multimorbidities, demography and viral variants on post-acute sequelae of COVID-19 (‘Long COVID’) in Dutch primary care: A retrospective cohort study - Matthijs S. Berends; Maarten Homburg; Thijmen Kupers; Eline N. Meijer; Isabelle Bos; Robert Verheij; Jeroen Kuiper; Marjolein Y. Berger; Lilian L. Peters (International Journal of Infectious Diseases)
Introduction: Post-acute sequelae of COVID-19 (PASC), or Long COVID, involves persistent symptoms following acute infection, posing a global health challenge. While a growing number of studies have investigated potential predictors and risk factors, uncertainties remain regarding their consistency and clinical applicability. This study investigates PASC prevalence, comorbidities, demographics and viral variants using Dutch primary care electronic healthcare records (EHR). Methods: A retrospective cohort study used EHR data from 59 general practices in the Northern Netherlands, including 19,638 SARS-CoV-2 PCR-positive patients from January 1, 2020, to December 31, 2021. PASC was identified via World Health Organization and CDC guidelines, a Dutch Word2Vec model, and clinical assessments. Relative risk (RR) calculations analysed comorbidities, demographics and viral variants. Results: PASC prevalence was 5.8% (95% CI: 5.4-6.1%). Comorbidities significantly increasing PASC risk included lung disease (RR: 1.95), cardiovascular disease (RR: 1.73), diabetes (RR: 1.82), kidney disease (RR: 1.98) and mental illness (RR: 1.29). Females and individuals aged ≥45 had increased risk. Multivariate regression revealed higher odds of prolonged PASC for ages 45-59 (adjusted odds ratios [AOR]: 3.02), 60-74 (AOR: 3.25) and 75+ (AOR: 2.44). Combined mental illness and lung disease further increased risk (AOR: 2.55). Conclusion: Chronic conditions, multimorbidity and demographics significantly influence PASC onset and duration. Targeted interventions may mitigate its long-term impact.